Peran Mediasi Religiusitas terhadap Keputusan Pembelian: Badan Kontak Majelis Taklim (BKMT) Kota Palopo - Ibnu Hajar; Nani Hamdani; Yuliana; Izza Nur Aulia; Saldi (Dinamis : Journal of Islamic Management and Bussiness, 2024)
This study aims to determine the influence of halal labels on the purchase decision of cosmetic products mediated by the religiosity of the empirical evidence of BKMT Palopo. The type of research used is quantitative to collect data from Muslim entrepreneurs with questionnaires and analyzed using Partial Least Square-Structural Equation Modeling. The findings of this study are that there is a significant relationship between the influence of halal labels on purchase decisions, halal labels on and regiliusness and there is a significant influence of religiosity on purchase decisions. This research can also provide deeper insights into consumer preferences that pay attention to halal aspects in the products they buy.